An Alternative to Natural Monopoly - Oriol Carbonell-Nicolau (Rutgers University, Department of Economics, 2019)
We consider a shared ownership arrangement among consumers/owners as a means to organize production with an underlying decreasing average cost function typical of natural monopolies. The resulting output allocation yields a lower deadweight loss than the monopoly allocation, and is, in some cases, efficient.
Keywords: L12; L13; 330; natural monopoly; deaweight loss from monopoly; decreasing average costs